2011
DOI: 10.1016/j.cub.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Loading of Meiotic Cohesin by SCC-2 Is Required for Early Processing of DSBs and for the DNA Damage Checkpoint

Abstract: We propose that meiotic cohesin promotes DSB processing and recruitment of DNA damage checkpoint proteins, thus implicating cohesin in the earliest steps of the DNA damage response during meiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 53 publications
(85 reference statements)
2
61
0
Order By: Relevance
“…Cornelia de Lange syndrome (CdLS) is a genetically dominant disorder caused by the mutation of one copy of NIPBL, SMC1, SMC3, or HDAC8 51 - 57 . A related disorder is caused by mutation of RAD21 58 .…”
Section: Cornelia De Lange Syndrome and Cancermentioning
confidence: 99%
“…Cornelia de Lange syndrome (CdLS) is a genetically dominant disorder caused by the mutation of one copy of NIPBL, SMC1, SMC3, or HDAC8 51 - 57 . A related disorder is caused by mutation of RAD21 58 .…”
Section: Cornelia De Lange Syndrome and Cancermentioning
confidence: 99%
“…Interestingly, it was recently shown that sister chromatid cohesion is not only required for ef fi cient repair of meiotic DSBs but that cohesin is also required for triggering DNA damage-induced germ cell apoptosis (Lightfoot et al 2011 ) . This function is likely to act very upstream in the DNA damage response cascade that leads to apoptosis induction, as HUS-1 is not appropriately localized to chromosomes upon treatment with ionizing irradiation (Lightfoot et al 2011 ) . ATM-and ATR-activation lead to the phosphorylation of downstream targets including Chk1 and Chk2, which initiates a secondary wave of phosphorylation events.…”
Section: Upstream Dna Damage Checkpoint Signalling In the C Elegans mentioning
confidence: 99%
“…In many organisms, disruption of components of the meiotic chromosome axes, including SYCP3 and cohesins, leads to a defect in MCN signaling (Wang and Hoog 2006;Kouz-netsova et al 2009;Callender and Hollingsworth 2010;Lightfoot et al 2011), although in some cases the loss of signal has been attributed to reduced DSB formation (Callender and Hollingsworth 2010). Perhaps not surprisingly, MCN roles have also been reported for several histone methyltransferases (San-Segundo and Roeder 2000;Checchi and Engebrecht 2011;Lamelza and Bhalla 2012;Ontoso et al 2013a,b), which presumably promote chromosome axis assembly or contribute to the structural environment of MCN signaling.…”
Section: The Context Mattersmentioning
confidence: 99%
“…For example, the S. cerevisiae axis protein Red1 physically associates with the 9-1-1 complex, an interaction required for MCN activity (Eichinger and Jentsch 2010). Cohesin is similarly required for the recruitment of the 9-1-1 complex in C. elegans (Lightfoot et al 2011). Furthermore, because the activation of CHK2 kinases by ATM/ATR typically requires the presence of adaptor proteins, it has been suggested that chromosome axis proteins may provide such an adaptor function for the activation of the MCN (Niu et al 2005;Carballo et al 2008;Hunter 2008;Eichinger and Jentsch 2010;Tougan et al 2010).…”
Section: The Context Mattersmentioning
confidence: 99%